Penatalaksanaan Fisioterapi Pada Kondisi Post Fraktur Antebrachii 1/3 Distal Sinistra Dengan Terapi Latihan Dan Massage Therapy Di Rsud Saras Husada Purworejo - NINGRUM, Hasti Kusuma, Maskun Pudjianto, SMPH (2015)
Background: Antebrachii fracture is a break contuinitas radius ulna bone. In children usually seem anterior angulation and both ends of the broken bone is still in touch with each other. In adults overview fractures usually obvious because often a fracture of the radius ulna fracture accompanied by dislocation of the bone fragments. Antebrachii fracture treatment can be done in two ways, namely by conservative and operative technique. Conservative techniques performed by administering casts, splints and traction. As for the operative performed by Open Reduction Internal Fixation ( ORIF ) with the mounting plate and screw. On condition post fracture antebrachii will cause various problems such as: pain, edema, decreased muscle strength, limitation range of motion (LGS), and functional impairment. Objective: To pinpoint the benefits of Exercise Therapy, Massage therapy and index woodsrock reducing pain, reduce edema, improve muscle strength, increase range of motion (LGS), and to improve the conditions of post- fractures functional antebrachii. Results: Decrease pain by using Visual Description Scale (VDS),for tenderness at T1 = 5 to T6 = 2. Pain motion T1 = 6 be T6 = 3. Increased range of motion for wrist T1 = S 350- 0-450 be T6 = 400- 0-500. For MCP (I) T1 = 00-0 -250 become T6 = 00 - 0-400. MCP (2) T1 = 00 - 0- 450 becomes T6 = 00 -0- 550 . MCP (3) T6 = 00 -0-370 becomes T6 = 00 -0- 450. MCP (4) T1= 30 -0- 250 become T6= 00 -0- 300. MCP (5) T1= 30 -0- 250 become T6= 60 -0- 400. MMT muscle strength with the results for flexion-extension wrist flexion T1= 4 and T6 = 4 Results: there has been no improvement. Motion supination and pronation. Supination T1= 2 becomes T6= 3. And pronation T1= 2 becomes T6= 3. Motion ulnar and radial deviation. Ulnar deviation T1= 3 and T6 = 4. Radial deviation T1 = 3 becomes T6 = 4. Flexion and extension of the fingers. Flexion Fingers becomes T1 = 3 becomes T6= 4. Extension fingers into T1= 3 becomes T6 = 4. Decrease in edema with stylodeus ulna processus benchmark point at T1 = 22 cm into T6 = 19 cm. stylodeus ulna processus pull 5 cm distal results: T1 = 24 cm into T6 = 21.5 cm. On 5 cm of the proximal to the point stylodeus ulna processus benchmark results: T1 = 23 cm into T6 = 20 cm. Conclusion: Exercise Therapy, Massage, and Index Woodsrock can reduce pain, Edema, improve LGS, increase muscle strength.